Modular design of bi- and multi-specific knob domain fusions - Kuravsky, Mikhail; Gibbons, Glyn F.; Joyce, Callum; Scott-Tucker, Anthony; Macpherson, Alex; Lawson, Alastair D. G. (Frontiers in Immunology, 2024)
Introduction The therapeutic potential of bispecific antibodies is becoming widely recognised, with over a hundred formats already described. For many applications, enhanced tissue penetration is sought, so bispecifics with low molecular weight may offer a route to enhanced potency. Here we report the design of bi- and tri-specific antibody-based constructs with molecular weights as low as 14.5 and 22 kDa respectively. Methods Autonomous bovine ultra-long CDR H3 (knob domain peptide) modules have been engineered with artificial coiled-coil stalks derived from Sin Nombre orthohantavirus nucleocapsid protein and human Beclin-1, and joined in series to produce bi- and tri-specific antibody-based constructs with exceptionally low molecular weights. Results Knob domain peptides with coiled-coil stalks retain high, independent antigen binding affinity, exhibit exceptional levels of thermal stability, and can be readily joined head-to-tail yielding the smallest described multi-specific antibody format. The resulting constructs are able to bind simultaneously to all their targets with no interference. Discussion Compared to existing bispecific formats, the reduced molecular weight of the knob domain fusions may enable enhanced tissue penetration and facilitate binding to cryptic epitopes that are inaccessible to conventional antibodies. Furthermore, they can be easily produced at high yield as recombinant products and are free from the heavy-light chain mispairing issue. Taken together, our approach offers an efficient route to modular construction of minimalistic bi- and multi-specifics, thereby further broadening the therapeutic scope for knob domain peptides.